2015
DOI: 10.1590/s1679-45082015rw3140
|View full text |Cite
|
Sign up to set email alerts
|

Femoral quadriceps neuromuscular electrical stimulation after total knee arthroplasty: a systematic review

Abstract: The purpose of this study was to evaluate the effects of neuromuscular electrical stimulation in patients submitted to total knee arthroplasty. This was a systematic review with no language or publication status restriction. Our search was made in Cochrane Library, MEDLINE, Embase and LILACS. Randomized or quasi-randomized clinical trials evaluating neuromuscular electrical stimulation after total knee arthroplasty were included. Four studies with moderate risk of bias and low statistical power were included, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
3
0
3
Order By: Relevance
“…They revealed that NMES improved the recovery of quadriceps strength after the knee surgery with grade B evidence ( 43 ). Due to limited pieces of relevant literature published, some other reviews also failed to examine the effect of NMES on MVIC following TKA ( 45 , 46 ). After including more RCTs that have been published recently, for the first time, we proved that NMES improved quadriceps muscle strength in terms of MVIC after TKA within 1 month, 1–2 months, 3–4 months, and 12–13 months with high-quality evidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They revealed that NMES improved the recovery of quadriceps strength after the knee surgery with grade B evidence ( 43 ). Due to limited pieces of relevant literature published, some other reviews also failed to examine the effect of NMES on MVIC following TKA ( 45 , 46 ). After including more RCTs that have been published recently, for the first time, we proved that NMES improved quadriceps muscle strength in terms of MVIC after TKA within 1 month, 1–2 months, 3–4 months, and 12–13 months with high-quality evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence to prove the advantage of NMES in TKA was limited. Given the insufficiency of available data for comparison, some other reviews failed to explore the quantized effect of NMES on TKA ( 43 , 44 , 46 , 57 , 58 ). As far as we knew, this was the first systematic review and meta-analysis to comprehensively explore the effect of NMES on quadriceps muscle strength, pain, and function following TKA.…”
Section: Discussionmentioning
confidence: 99%
“…Однако в отдаленные сроки, через 12 мес. и более после завершения выполнения программ кинезиотерапии, различия в изученных показателях между участниками экспериментальной и контрольной групп нивелировались [7,29]. При наличии более однородной и, соответственно, более надежной доказательной базы эти результаты можно интерпретировать как ускорение восстановления опорно-кинематической функции нижних конечностей после эндопротезированния коленного сустава вследствие благоприятного воздействия программ кинезиотерапии в ближайшие сроки после операции [30].…”
Section: результаты и их обсуждениеunclassified
“…Необходимо отметить, что ни в указанной [14], ни в других научных работах [26][27][28] не сообщается о контрактуре или отеке в области сустава. Это снижает достоверность полученных авторами результатов положительного воздействия физических упражнений [29,50] и ограничивает показания к применению данной методики восстановления функциональных возможностей мышц, стабилизирующих коленный сустав. Таким образом, разработка протокола кинезиотерапии с адекватной физической нагрузкой, направленной, в частности, на преодоление нейромышечных изменений у пациентов после эндопротезирования коленного сустава, требует систематизации на основе научно обоснованного подхода.…”
Section: результаты и их обсуждениеunclassified
“… 7 , 8 ) The strength of the knee extensor has crucial effects on the symptoms of bone and joint disorders, such as knee osteoarthritis and anterior cruciate ligament (ACL) injury. 4 , 9 , 10 ) However, evidence for the efficacy of NMES in these diseases has not been fully established. Several systematic reviews and clinical guidelines have mentioned that the broad range of available stimulation modalities prevents the accumulation of consistent evidence.…”
Section: Introductionmentioning
confidence: 99%